eラーニングによる学習効果の検討: Moodle上での学習データと意識調査の分析 - 白鳥, 亜矢子; 志村, 昭暢; 山岸, 拓; 中村, 香恵子; 横山, 吉樹; 竹内, 典彦; 石塚, 博規; 尾田, 智彦 (北海道英語教育学会 紀要, 2011)
The purpose of this study is to investigate the following two questions: (1) Does e-Learning help students improve their English skills and does English improvement differ according to the level of the students' English proficiency? (2) Does e-Learning change the students' attitude toward English learning and does their attitudinal change differ according to the students' level of English proficiency? The study was conducted at university A with students of a higher English proficiency, and university B with students of a lower English proficiency based on scores of pre- and post-English proficiency tests. The data was collected through pre- and post-tests and pre- and post-attitude surveys with thirty-one questions to be answered. Regarding the first research question, the results of this study showed that statistically there is a significant difference between pre- and post-tests at both universities, even though the difference is relatively limited. Therefore, it was found that e-Learning helps students improve their English skills to some extent. In terms of the English improvement, since the level of score improvement was found to be approximately the same between these two universities, no difference was identified. In regard to the second question, the study revealed that statistically no significant difference could be identified between pre- and post-attitude surveys at university A. On the other hand, there was a significant difference at university B for the following statement on the questionnaire:"The use of ICT during the class improves my English skills." Therefore, the results could imply that using e-learning helps students with a lower English proficiency to have a more positive-based attitude toward English learning.